2016
DOI: 10.3727/096368915x689749
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as an Antioxidant for Stroke Neuroprotection

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) is a hormone derived from the pineal gland that has a wide range of clinical applications. While melatonin was originally assessed as a hormone specializing in regulation of the normal circadian rhythm in mammals, it now has been shown to be an effective free radical scavenger and antioxidant. Current research has focused on central nervous system (CNS) disorders, stroke in particular, for potential melatonin-based therapeutics. As of now, the realm of potential therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 76 publications
1
38
0
1
Order By: Relevance
“…Melatonin is considered one of the most potent antioxidant, playing an important protective role in ischaemic injury (see Figure ; Watson, Diamandis, Gonzales‐Portillo, Reyes, & Borlongan, ; Wu et al, ). In middle cerebral artery occlusion (MCAO), a model of acute ischaemia in rats, receiving pineal gland transplantation improves the motor outcome and decreases the infarct size through the secretion of melatonin (Borlongan et al, ).…”
Section: Neurological Conditions and Melatoninmentioning
confidence: 99%
“…Melatonin is considered one of the most potent antioxidant, playing an important protective role in ischaemic injury (see Figure ; Watson, Diamandis, Gonzales‐Portillo, Reyes, & Borlongan, ; Wu et al, ). In middle cerebral artery occlusion (MCAO), a model of acute ischaemia in rats, receiving pineal gland transplantation improves the motor outcome and decreases the infarct size through the secretion of melatonin (Borlongan et al, ).…”
Section: Neurological Conditions and Melatoninmentioning
confidence: 99%
“…It also has therapeutic potential for respiratory, colonic, autoimmune, adult-onset chronic non-communicable diseases, ischemic brain and cardiovascular injury, circadian disturbance, stroke, steatohepatitis, etc. [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Melatonin can efficiently scavenge a variety of ROS including hydrogen peroxide (H 2 O 2 ), hydroxyl radical (HO•), nitric oxide (NO•), singlet oxygen ( 1 O 2 ) and superoxide anion (O 2– •) [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…During ischemia, excess ROS are generated and contribute to injury [25][26][27][28] . Melatonin is a potent antioxidant molecule that has been reported to have a protective eff ect during ischemia [9,10,29] . Melatonin receptors (mainly MT1 and MT2) are widely distributed in the mammalian CNS, hippocampus, caudate putamen, suprachiasmatic nucleus (SCN), paraventricular nucleus, periventricular nucleus, supraoptic nucleus, substantia nigra, mammillary bodies, retinas, nucleus basalis of Meynert, nucleus accumbens, and tuberomammillary nucleus [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is a neurohormone secreted from the pineal gland and plays a wide range of regulatory roles in the mammalian body such as the regulation of circadian rhythm [8] . It is also reported that melatonin is a potent antioxidant agent and has shown promising results as a therapeutic intervention in ischemic studies [3,6,7,9,10] . Melatonin receptors (MT1 and MT2) are widely distributed in the CNS [6] .…”
Section: Introductionmentioning
confidence: 98%